2007
DOI: 10.1007/s10646-007-0165-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis of herbicide quinclorac residues in irrigated rice areas, Santa Catarina, Brazil

Abstract: Deterministic and probabilistic risk analyses were carried out for seven hydrographic basins in the State of Santa Catarina (Brazil), where irrigated rice is cultivated. Monitoring studies conducted in 1998/1999 and 1999/2000 had found that the herbicide quinclorac was the most frequently detected agrochemical residue, occurring in five of the seven hydrographic basins. In order to assess the ecological risk posed by quinclorac, median lethal concentration (LC(50)) and median effective concentration (EC(50)) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 9 publications
1
14
0
1
Order By: Relevance
“…A avaliação de estudos sobre o comportamento dos agroquímicos no ambiente em conjunto com resultados obtidos em bioensaios, realizados com diferentes organismos-teste, assume extrema importância para a criteriosa análise do risco potencial de impacto desses compostos sobre o meio ambiente (RESGALLA JR. et al, 2007).…”
Section: Tabela 2 -Mecanismo De Ação Dos Herbicidas Testados E Seu Efunclassified
“…A avaliação de estudos sobre o comportamento dos agroquímicos no ambiente em conjunto com resultados obtidos em bioensaios, realizados com diferentes organismos-teste, assume extrema importância para a criteriosa análise do risco potencial de impacto desses compostos sobre o meio ambiente (RESGALLA JR. et al, 2007).…”
Section: Tabela 2 -Mecanismo De Ação Dos Herbicidas Testados E Seu Efunclassified
“…However, some grass weeds such as barnyard grass ( Echinochloa crusgalli ) significantly reduce the world's rice yield. Quinclorac (3,7-dichloro-8-quinolinecarboxylic acid) is a herbicide with specific selectivity between annual grass weeds and some graminaceous crops (Koo et al, 1996 ; Resgalla et al, 2007 ). Quinclorac is a compound of the chemical group of quinolines with toxicological class III (low toxicity), and in the recent years, it has been widely used on paddy rice fields to effectively control barnyard grass (Resgalla et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Quinclorac (3,7-dichloro-8-quinolinecarboxylic acid) is a herbicide with specific selectivity between annual grass weeds and some graminaceous crops (Koo et al, 1996 ; Resgalla et al, 2007 ). Quinclorac is a compound of the chemical group of quinolines with toxicological class III (low toxicity), and in the recent years, it has been widely used on paddy rice fields to effectively control barnyard grass (Resgalla et al, 2007 ). Quinclorac is a highly selective auxin-type herbicide, originally emerged from lead optimization with more than 3000 synthesized derivatives by BASF and was introduced into rice cultivation systems in 1988 (Haden et al, 1985 ; Grossmann, 2000b , 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because local data are often lacking, risk assessments are also often based on data from other regions that, depending on the protection goals, can raise additional uncertainties and concerns as to whether this yields appropriate assessments. Few studies on risk assessment of pesticides for Latin America aquatic ecosystems are reported in the literature (Barra et al 2000;Waichman et al 2002;Resgalla et al 2007;Venturino et al 2007;Ronco et al 2008;Waichman 2008;Tosi et al 2009;Di Marzio et al 2010;Rico et al 2011;Chelinho et al 2012;Martini et al 2012;Schiesari et al 2013).…”
Section: Introductionmentioning
confidence: 99%